2002
DOI: 10.1046/j.1524-475x.2002.10402.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of transcutaneous oxygen tension measurement in diabetic lower extremity ulcers treated with hyperbaric oxygen therapy: a retrospective analysis of 1144 patients

Abstract: The objective of this retrospective analysis was to determine the reliability of transcutaneous oxygen tension measurement (TcPO2) in predicting outcomes of diabetics who underwent hyperbaric oxygen therapy for lower extremity wounds. Six hyperbaric facilities provided TcPO2 data under several possible conditions: breathing air, breathing oxygen at sea level, and breathing oxygen in the chamber. Overall, 75.6% of the patients improved after hyperbaric oxygen therapy. Baseline sea-level air TcPO2 identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 14 publications
3
117
0
3
Order By: Relevance
“…Similar results have been reported by others. In a study by Fife et al, 629 patients with basal TcPO 2 below 25 mmHg were less likely to benefit from HBOT than those with higher TcPO 2 values [9]. Wattel et al reported a mean basal TcPO 2 of 32 mmHg in healers (n=15), compared with 12 mmHg in non-healers in a case-series of 20 patients (11 with diabetes and nine arterial insufficiency without diabetes) given adjunctive treatment with HBOT [10].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by others. In a study by Fife et al, 629 patients with basal TcPO 2 below 25 mmHg were less likely to benefit from HBOT than those with higher TcPO 2 values [9]. Wattel et al reported a mean basal TcPO 2 of 32 mmHg in healers (n=15), compared with 12 mmHg in non-healers in a case-series of 20 patients (11 with diabetes and nine arterial insufficiency without diabetes) given adjunctive treatment with HBOT [10].…”
Section: Discussionmentioning
confidence: 99%
“…The comparisons with transcutaneous oximetry (TcO 2 ) are important because, although it is currently widely used and accepted as useful by some clinicians, 115,116,117 even its most vocal proponents would welcome a more accurate technique. Despite several limitations, it is the current standard for evaluating capacity to heal in ischemic ulcers.…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…However, the rise at 1.5 ATA was encouraging and suggestive of potential benefit of hyperbaric oxygen therapy. 7 Magnetic resonance angiogram showed the abdominal aorta, bilateral iliac, femoral, and popliteal arteries to be free of significant arterial disease. The trifurcation vessels were diseased, however, with extensive occlusion of the tibialis anterior and peroneal arteries without significant reconstitution ( Figure 3).…”
Section: Case Reportmentioning
confidence: 99%